The case for miracles [compact disc, unabridged] : a journalist investigates evidence for the supernatural - Strobel, Lee, 1952- (Zondervan, 2018)
Lee Strobel trains his investigative sights on the hot-button issue of whether it's credible to believe God intervenes supernaturally in people's lives today.